Lista comentada de plantas de la Estación de Biología Tropical "Los Tuxtlas", Veracruz, México: (Violaceaea-Zingiberaceae) - Ibarra-Manríquez, Guillermo (1996)
This is the third and final part of the commented list of plants found in Los Tuxtlas, a Mexican Tropical Biology Research Station.Previous parts appeared in Revista de Biologia Tropical vol. 43 ( 1 -3) and vol. 44 ( 1 ).